Supplier–customer relationships: A case study of power dynamics. Issue 4 (December 2015) - Lacoste, Sylvie; Johnsen, Rhona E.
Abstract: Against the backdrop of earlier research on power in supplier–customer relationships, our study focuses on the power dynamics, which lead low-power suppliers to re-balance their power relationship with strategic customers. An in-depth qualitative study is used to examine the case of a network made of several dyads (FMCG strategic customers/corrugated packaging suppliers). Our findings are slightly counter-intuitive: a new stream of literature tends to show that supplier performance is relationship-driven. We find here that the supplier performance is process-driven: to reach the targeted level of performance and to move out from a low-power position, the suppliers develop a two-step process. First, suppliers shift their focus from a product centric approach to a customer business process one, supplying "Process Support Services". Second, suppliers initiate "Performance Process Services" to position themselves to outsource the customer's business processes, hence creating interdependency and a countervailing power with the strategic customer. Highlights: We study how low-power suppliers re-balance the power dynamic with strategic customers. Suppliers develop a two-step service process to create a countervailing power. The study highlights some counterintuitive findings on supplier performance driver.